Contraceptive decision-making among currently married couples in Kerala: a mixed-methods study - Mukundhan, Anusree K.; Thomas, Sunu C. (International Journal Of Community Medicine And Public Health, 2025)
Background: Contraceptive decision making refers to the ability of a women freely choose the contraceptive method they desired through the process of informed decision-making by effectively minimizing unnecessary pressure from important others. Women’s autonomy is often constrained by gender power imbalances and sociocultural norms. In Kerala, despite better educational and economic status, limited evidence suggests these advantages enhance their decision-making regarding contraception. Methods: A community-based mixed-methods study was conducted in Thrissur and Thiruvananthapuram districts in Kerala. Multistage cluster sampling was employed in both the districts to get a total sample of 330 for the quantitative component. Bivariate and multivariable logistic regression were done to estimate the proportion and associated factors. Additionally, 19 in-depth interviews were conducted using purposive sampling to explore decision-making dynamics. Results: Only 18.2% of women reported making contraceptive decisions independently. Employed women (APR: 2.94, 95% CI: 1.84–4.71, p<0.001) and women with both male and female children were more likely to decide independently (APR: 2.80, 95% CI: 1.46–5.30, p=0.002). Qualitative findings highlighted decision-making process among couples are often hindered due to couples’ limited knowledge, misconceptions and fear of side effects. Conclusions: In Kerala, independent contraceptive decision-making among women remains relatively low. Limited knowledge hindered women’s ability to negotiate contraceptive use with their partners, often conform to prevailing social norms. Thus, interventions and policies should focus on raising awareness along with empowering women through financial independence and addressing deep-rooted social and gender norms.